Writing - Brieger, Nick (Tổng hợp, 2014)
Write clearer business documents more efficiently This brand new self-study book is the ideal way for business people to refine and perfect their written English. It is aimed particularly at executives who communicate in written English frequently or work in foreign or multinational companies